P202 Evaluation of a latent tuberculosis infection screening and treatment programme for recent migrants. (12th November 2019) - O'Brien, K; Ikram, S; Burman, M; Rahman, A; Kunst, H
Abstract : Introduction and objectives: Since 2014, the London borough of Newham has been a pilot for the national latent tuberculosis infection (LTBI) screening and treatment programme for recent migrants. Effective delivery of the programme requires collaboration between multiple stakeholders across primary and secondary care; we sought to understand the lessons learned from 5 years of running the service. Methods: We performed semi-structured interviews with nine multi-level stakeholders involved in the implementation and delivery of the programme. This included individuals from the Clinical Commissioning Group, NHS England and the local pharmaceutical committee. Interviews were organised around predetermined, open style questions and were carried out during the period 15th- 30thMay 2019. Results: Several barriers and facilitators to programme implementation and delivery were identified (table 1). Facilitators included effective communication between multi-level stakeholders, with those interviewed placing emphases on continuous review and training of service providers. Aggregate data collection, processing and monitoring was considered a significant facilitator. TB and LTBI education through healthcare providers and novel educational tools, was also cited as an important facilitator. The main challenges identified included communication between healthcare providers, estimations of testing and treatment uptake and perceived low levels of patient knowledge of TB or LTBI. Conclusion: To achieve the national goal of systematic screening and treatment of recent migrants for LTBI will require high quality services to be established across the country. It is vital to share learning as the programme develops. Evaluation of a large programme in East London identified that a continuous programme of education, close collaboration between stakeholders and continuous aggregate data collection were felt to be vital for successful outcomes.